Peran G7 sebagai Komunitas Internasional dalam mengatasi Krisis Pangan Dunia akibat Konflik Rusia-Ukraina - Syarif, Yusran; Al Farauqi, Mohamad Dziqie Aulia; Tyas, Intan Kinanthi Damarin (Department of International Relations, Universitas Mulawarman, 2025)
The conflict between Russia and Ukraine did not just happen, this conflict has its roots in the internal political crisis in Ukraine and the intervention by the Russian military in the Crimean Peninsula which caused serious tensions between the two countries. Then the Russian invasion of Ukraine in 2022 has generated international condemnation and deep concern about the political, economic and humanitarian consequences it will cause. The international community of course condemned Russia's actions as a violation of international law and Ukraine's sovereignty, and also the conflict between these two countries will lead to a world food crisis where Russia and Ukraine are known as one of the world's agricultural product importers. for that the international community response to this invasion is very important. G7 as one of the international communities consisting of 7 countries with advanced economies plays a role in providing financial, medical, food assistance and protection for millions of people who are affected. And also the international community seeks to deal with conflicts and violations of state sovereignty. Either diplomatically or sanctions against Russia to stop its invasion of Ukraine, And also the solution related to food insecurity cannot only be overcome by opening free market access alone. because it is not only related to this war, the possibility of changes in weather and climate will also have an impact on world agricultural output For this reason, the G7 is making efforts for both Ukraine and the countries affected by this conflict to survive world food insecurity.